Evaluation Of Vehicle Loading Procedures At KMP.Gambolo and Kmp. Ambu-Ambu in Teluk Bungus Port, West Sumatera Province - Rudy Sugiharto; Noor Sulistiyono; Budi Kusuma (IWJ : Inland Waterways Journal, 2021)
Bungus Bay Crossing Port is one of the ferry ports in West Sumatra Province, has a very strategic position and to support the regional economy.but there are still many finding procedures for loading that are not in accordance with PM 115/2016. The method used in this research is Gap Analysis as a comparison between the existing condition and the expected conditions and focuses on the current gap with the targeted conditions